Working Capital Management and Bank Profitability: Evidence from Indonesian Listed Banks - Sujono; Anggy Wardhani Ruslan; Harmiati Bahar (Lembaga Publikasi Ilmiah Nusantara, 2026)
When banks don't make enough money, their capacity to function as a middleman, their internal capital, and their liquidity all get weaker. This study examines whether indicators of working capital and liquidity management clarify the disparities in Return on Assets (ROA) among banks listed on the Indonesia Stock Exchange. This study included Current Ratio (CR), Loans/Advances to Total Assets (LATA), Current Assets to Total Assets (CATA), Current Liabilities to Total Assets (CLTA), and Loan to Deposit Ratio (LDR) as explanatory variables. This study utilizes balanced panel data from 29 banks for the period 2019–2023, encompassing 145 bank-year observations. This research estimates panel data regression and use the Hausman test to select the fixed effects model. This study use robust standard errors to address indications of heteroscedasticity and autocorrelation. The results show that LATA has a big positive effect on ROA. The results show that LDR has a big negative effect on ROA. The results show that CR, CATA, and CLTA do not have a big effect on ROA. The discussion links the LATA results to the enhancement of productive assets. The conversation links the LDR results to the trade-off between making money and having enough cash on hand when credit growth puts pressure on the liquidity buffer. The results demonstrate that a combination of productive assets and liquidity discipline is more significant for ROA than static liquidity ratios.